A Case of Access: Inuvialuit Engagement with the Smithsonian's MacFarlane Collection (Full Report) - Charles Arnold; A Case of Access" Project Team" (Simon Fraser University, 2014)
The final report from "A Case of Access", an IPinCH Community Initiative.